Orchestrating forest policy-making: involvement of scientists & stakeholders in political processes in Europe - Secco, Laura; Wallin, Ida; Sergent, Arnaud; Pülzl, Helga; Kleinschmit, Daniela (Natural Resources Institute Finland, Luke, 2016)
Forest policy making processes in Europe can nowadays be characterized as multi-level and multi-sectorial governance processes, in which involved actors have an increasingly complex and gradually more contextually defined relationship. Boundaries between and within public, private and civic actors have become blurred and the role of scientists has changed, as other forms of expertise (e.g. practitioners, laypersons expertise but also citizen science) have become relevant. Working Group 3 (WG3) of COST Action FP1207 ORCHESTRA has worked with the aim of exploring these issues and stimulating a debate about participatory-based forest policy making processes. A survey at national and sub-national level in all involved countries, an international conference and a Special Issue within Forest Policy and Economics have been conducted. Results suggest that “orchestrating” forest-policy making can be a “mission impossible” (Pregernig, 2015) if not enough attention is deserved to procedural arrangements and policy makers commitment. Further research is needed to find out additional and systematic evidences of effectiveness of adopting participatory approaches, taking into consideration the potentially important (but often disregarded) roles played by scientists and citizens in influencing political processes.
Keywords: network governance; participatory governance; forest policy; science-policy-society interface